Over-education in the Labor Market: Determinants and Consequences in Perú 2001-2011 - Rodríguez Lozano, Efraín (2016)
The marked increase in the Peruvian population’s access to different forms of higher education in the last decade has been accompanied by a decline in real income among the group of workers that had access to university education. Therefore, those characteristics shared by workers whose level of education exceeds what is required for their occupation (over-educated workers), and theextent to which this is associated with receiving lower income on the job market, are explored. A data pool from the National Household Survey (Encuesta Nacional de Hogares) for the years 2001 to 2011, and a panel from the same survey for 2007 to 2011, are analyzed. The estimation of logit models shows evidence that living in rural areas, working at companies with less thanten employees, being salaried, among other characteristics, are positively associated with the probability of being over-educated. The results on income are estimated by way of the models of Verdugo and Verdugo and of Duncan and Hoffman, using both cross-sectional and panel data (by way of fixed effects and instrumental variables). In the case of workers with higher education, it is found that over-education can be associated with salaries that are lower by more than 13 percentage points. This analysis is performed for four different over-education identification methodologies.